An Experimental Study of Jute FIBRE Reinforced Concrete By Partial Replacement Cement With Rice Husk Ash - Ratnakar Mishra; Mr. Anuj K. Sharma; Dr. Sushant Kumar (Revista Electronica de Veterinaria, 2024)
This research paper is all about the experimental utilization of jute fiber and rice husk ash as partial substitutes for cement in concrete formulations. Aim of this experimental study is to explore eco-friendly alternatives in construction materials. Jute fiber, known for its considerable tensile strength and environmental compatibility, and rice husk ash, rich in reactive silica, are proposed as reinforcements to enhance the mechanical properties of concrete, such as its compressive strength and resistance to shrinkage cracks. The investigation encompasses a detailed assessment of these materials' effects on concrete, focusing on optimizing the mix proportions to achieve desired strength and durability while also conducting a comprehensive analysis of the cost implications and environmental benefits. This experimental study not only underscores the potential of utilizing agricultural waste in mitigating the environmental impacts associated with construction materials but also highlights the economic advantages of adopting such sustainable alternatives in the construction industry.